Diskursus Pemikiran Al-Jahiz Mengenai Gangguan Berbahasa - Ilyas, Muhammad Azizzullah (Sekolah Tinggi Agama Islam (STAIN) Curup, 2018)
The study of language pathology has been going on longer and developing with the development of language studies, the problems encountered in learning speaking skills are often related to speech skills which sometimes enter the language pathology area which requires educator knowledge especially the interference of Arabic learners. This study aims to analyze speech problems and language in the classical study represented by Al-Jahiz seen through the perspective of modern linguistics. This study uses a qualitative approach with library data sources, descriptive analysis is done by reading the content and analyzed. The results showed that Al-Jahiz's views were divided into speech disorders and language disorders; lusghah, luknah, lahn and ayy. Jahiz saw lahn as the worst speech disorder, and he assumed that in lahn is not only caused by articulation factors and motor aphasia but can also be driven by personal factors to replace sounds that are difficult to pronounce with light sounds.